Preparation method of cobalt salt type adhesion promoter

The method addresses low anti-humidity aging of cobalt salt adhesion promoters by ensuring a nitrogen-rich reaction environment and precise spray drying adjustments, resulting in improved adhesion and mechanical stability in humid conditions.

CN119220198AInactive Publication Date: 2024-12-31朝阳市征和化工有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411712343.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing cobalt salt-based adhesion promoters exhibit low anti-humidity aging performance, which affects their stability and reliability in humid environments.

Method used

A method involving a nitrogen environment for mixing raw materials, esterification and coordination reactions, followed by spray drying, with adjustments based on color and state change evaluation values to enhance the anti-wet aging performance of cobalt salt adhesion promoters.

Benefits of technology

The method provides a stable, oxygen-free reaction environment, improving the adhesion and mechanical properties of cobalt salt adhesion promoters in humid conditions by enhancing their anti-wet aging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220198A_ABST
    Figure CN119220198A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesion promoters, in particular to a preparation method of a cobalt salt type adhesion promoter, which comprises the following steps: in a nitrogen environment, mixing a plurality of raw materials to obtain a mixed solution, carrying out esterification reaction on the mixed solution to obtain a modified bisphenol A epoxy resin solution, a modified bisphenol A epoxy resin solution and a cobalt boroacylate solution are mixed to obtain a reaction solution, the reaction solution is subjected to spray drying to obtain the cobalt salt adhesion promoter, and the drying qualification of the cobalt salt adhesion promoter is determined based on a color expression evaluation value of the cobalt salt adhesion promoter. And determining an adjusting strategy of the spray drying process based on the state change evaluation value of the cobalt salt adhesion promoter, selecting a dried and qualified cobalt salt adhesion promoter sample to carry out a wet aging resistance test, and adjusting the reaction rate of the esterification reaction under the condition that the wet aging resistance of the cobalt salt adhesion promoter is determined to be unqualified. The wet aging resistance of the cobalt salt adhesion promoter is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesion promoters, and in particular to a method for preparing a cobalt salt type adhesion promoter. Background Art

[0002] Cobalt salt-based adhesion promoter is a direct-addition adhesive widely used for efficient bonding between rubber and metal. With the development of the rubber industry, especially the rapid growth of rubber products such as radial tires, steel wire reinforced conveyor belts, steel braided hoses and rubber rollers, the demand for efficient and stable adhesion promoters continues to increase. Cobalt salt-based adhesion promoters have been widely used in these fields due to their excellent adhesion and stability. Bisphenol A epoxy resin is a polymer compound formed by the polycondensation of bisphenol A and epichlorohydrin under the action of an alkaline catalyst. The epoxy and hydroxyl groups in its molecular structure give the resin reactivity, so that the resin cured product has strong cohesion and adhesion. In the field of adhesives, bisphenol A epoxy resin, as a key component, can give the adhesive strong adhesion and excellent aging resistance, ensuring the long-term stability and reliability of the bonded joint.

[0003] Chinese patent application publication number: CN101481591A discloses a method for preparing an organic cobalt salt adhesion promoter, which comprises respectively preparing a cobalt solution, a sodium hydroxide solution and a sodium carbonate solution of a certain concentration; after heating the cobalt solution, slowly adding the sodium hydroxide solution until the pH value of the reaction solution is 7, and then slowly adding the sodium carbonate solution until the pH value of the reaction solution is 9.5; the reaction solution is allowed to stand, and the precipitate is rinsed with water; the rinsed precipitated inorganic cobalt salt is dehydrated twice, and then reacted with a weak organic acid in an organic solvent to obtain an organic cobalt salt adhesion promoter. However, the prior art has the following problems: in the prior art, no modified organic polymer is used to mix with the cobalt salt adhesion promoter to improve the anti-aging performance of the cobalt salt adhesion promoter, especially the anti-humidity aging performance is not improved, thereby resulting in the problem that the anti-humidity aging performance of the cobalt salt adhesion promoter is low. Summary of the invention

[0004] To this end, the present invention provides a method for preparing a cobalt salt type adhesion promoter, so as to overcome the problem of low anti-humidity aging performance of the cobalt salt adhesion promoter in the prior art.

[0005] To achieve the above object, the present invention provides a method for preparing a cobalt salt type adhesion promoter, comprising: Step S1, in a reactor with a preset nitrogen introduction rate under a nitrogen environment, a plurality of raw materials are mixed and stirred to fully mix the components to form a uniform mixed solution, wherein the raw materials include bisphenol A epoxy resin, a modifier, acetone, and a catalyst; Step S2, heating the mixed solution to a preset esterification reaction temperature and maintaining the temperature for a preset esterification time to perform an esterification reaction to obtain a modified bisphenol A epoxy resin; Step S3, cooling the modified bisphenol A epoxy resin to room temperature, and separating the modified bisphenol A epoxy resin from the unreacted raw material by distillation to obtain a purified modified bisphenol A epoxy resin solution; Step S4, mixing the modified bisphenol A epoxy resin solution with the cobalt boroacylate solution to obtain a reaction solution, heating the reaction solution to a preset coordination reaction temperature and maintaining the temperature for a preset coordination reaction time to perform a coordination reaction; Step S5, spray drying the reaction solution after the coordination reaction to obtain a cobalt salt adhesion promoter, and determining the eligibility of the drying of the cobalt salt adhesion promoter based on the color performance evaluation value of the cobalt salt adhesion promoter; Step S6, under the condition that the drying of the cobalt salt adhesion promoter is determined to be unqualified, determining the adjustment strategy of the spray drying process based on the state change evaluation value of the cobalt salt adhesion promoter, the adjustment strategy comprising increasing the drying pressure of the spray drying process or increasing the drying temperature of the spray drying process; Step S7, selecting a dried qualified cobalt salt adhesion promoter sample and placing it under preset relative humidity and preset temperature conditions for a preset time, performing a moisture aging resistance test on the cobalt salt adhesion promoter sample, and obtaining moisture aging resistance test data, calculating a moisture aging resistance effect characterization parameter according to the moisture aging resistance test data, and determining the qualification of the moisture aging resistance performance of the cobalt salt adhesion promoter; Step S8, when it is determined that the moisture aging resistance of the cobalt salt adhesion promoter is unqualified, adjusting the preset nitrogen introduction rate.

[0006] Furthermore, in step S1, the nitrogen introduction rate is preset to 50 mL / min.

[0007] Furthermore, in step S2, the preset esterification reaction temperature range is 80° C.-100° C., and the preset esterification time is 2.5 h.

[0008] Furthermore, in step S3, the room temperature ranges from 20°C to 25°C.

[0009] Furthermore, in step S4, the preset coordination reaction temperature range is 60° C.-90° C., and the preset coordination reaction time is 2 hours.

[0010] Further, in step S5, based on the comparison result that the color performance evaluation value of the cobalt salt adhesion promoter is less than or equal to the preset color performance evaluation value, it is determined that the drying of the cobalt salt adhesion promoter is unqualified, and the color performance evaluation value is calculated according to the formula:

[0011] Among them, P represents the color performance evaluation value, S represents the color saturation of the cobalt salt adhesion promoter, L represents the brightness of the cobalt salt adhesion promoter, L0 represents the brightness of the dried and qualified cobalt salt adhesion promoter, and D represents the color spot of the cobalt salt adhesion promoter.

[0012] Further, under the condition that the drying of the cobalt salt adhesion promoter is determined to be unqualified, it is determined to increase the drying temperature of the spray drying process based on the comparison result that the state change evaluation value of the cobalt salt adhesion promoter is less than or equal to the preset state change evaluation value, and it is determined to increase the drying temperature of the spray drying process by a preset temperature adjustment coefficient according to the comparison result that the difference between the preset state change evaluation value and the state change evaluation value is less than or equal to the preset difference, and the state change evaluation value is calculated according to the formula,

[0013] Among them, Q represents the state change evaluation value, C represents the cobalt salt adhesion promoter curing hardness value, C0 represents the preset cobalt salt adhesion promoter curing hardness value, R represents the cobalt salt adhesion promoter particle dispersion uniformity value, and R0 represents the preset particle dispersion uniformity value.

[0014] Further, under the condition that the drying of the cobalt salt adhesion promoter is determined to be unqualified, it is determined to increase the drying pressure of the spray drying process based on the comparison result that the state change evaluation value of the cobalt salt adhesion promoter is greater than the preset state change evaluation value, and it is determined to increase the drying pressure of the spray drying process by a preset pressure adjustment coefficient based on the comparison result that the ratio of the preset state change evaluation value to the state change evaluation value is less than or equal to the preset ratio.

[0015] Furthermore, in step S7, the moisture aging resistance test data includes adhesion test data, hardness test data, and tensile strength test data, the preset relative humidity range is 70%-90%, the preset temperature range is 40°C-60°C, and the preset time is 40h-48h.

[0016] Further, based on the comparison result that the anti-moisture aging effect characterization parameter is less than or equal to the preset anti-moisture aging effect characterization parameter, it is determined that the anti-moisture aging performance of the cobalt salt adhesion promoter is unqualified, and based on the comparison result that the relative difference is less than or equal to the preset relative difference, it is determined to increase the preset nitrogen introduction rate by the rate increase coefficient, and the relative difference is the relative difference between the anti-moisture aging effect characterization parameter and the preset anti-moisture aging effect characterization parameter.

[0017] Compared with the prior art, the beneficial effect of the present invention lies in that, in a nitrogen environment, the present invention can effectively exclude oxygen and other impurity gases in a reaction system, prevent reactants from reacting with oxygen in the air, and provide a stable, oxygen-free reaction environment for an esterification reaction. A plurality of raw materials are mixed to obtain a mixed solution, an esterification reaction is carried out, and then the mixed solution is mixed with a cobalt borate solution to obtain a reaction solution. The reaction solution is spray-dried to obtain a cobalt salt adhesion promoter. The cobalt salt adhesion promoter is tested for its anti-wet aging performance, so that the cobalt salt adhesion promoter can still maintain excellent adhesion and mechanical properties in a humid environment, thereby improving the anti-wet aging performance of the cobalt salt adhesion promoter.

[0018] Furthermore, the present invention sets esterification reaction conditions under nitrogen protection to ensure that the bisphenol A epoxy resin and the modifier fully react to form a modified bisphenol A epoxy resin. Under the set coordination reaction conditions, cobalt borate is introduced into the modified bisphenol A epoxy resin, which is converted into a cobalt salt adhesion promoter by spray drying technology, and the color performance evaluation value is used to quickly dry the eligibility. The cobalt salt adhesion promoter can still maintain stable adhesion in a humid environment, thereby improving the anti-wet aging performance of the cobalt salt adhesion promoter.

[0019] Furthermore, the present invention adjusts the temperature or pressure in the spray drying process by comparing the state change evaluation value with the preset state change evaluation value, and further refines the temperature adjustment strategy according to the difference between the state change evaluation value and the preset value to ensure that the drying effect meets the standard. This adjustment strategy based on the state change evaluation value can accurately identify the reasons for unqualified drying and take targeted measures. Through the refined temperature adjustment coefficient, fine control of the spray drying process is achieved, effectively improving the drying efficiency and the quality of the cobalt salt adhesion promoter.

[0020] Furthermore, the present invention ensures the durability and stability of the cobalt salt adhesion promoter in the actual application environment by conducting a moisture aging resistance test on the dried and qualified cobalt salt adhesion promoter and evaluating its moisture aging resistance by comparing the test data with the preset standard. By simulating the hot and humid environment under actual use conditions, potential performance degradation problems can be discovered in advance, thereby improving the overall quality and reliability.

[0021] Furthermore, the present invention improves the moisture aging resistance of the unqualified cobalt salt adhesion promoter by adjusting the nitrogen introduction rate, so as to improve the cobalt salt adhesion promoter to maintain excellent adhesion performance in a humid environment, thereby improving the moisture aging resistance of the cobalt salt adhesion promoter. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a flow chart of a method for preparing a cobalt salt type adhesion promoter according to an embodiment of the present invention; Figure 2A flow chart for determining the eligibility of a cobalt salt adhesion promoter to dryness for an embodiment of the present invention; Figure 3 A flow chart for determining a regulation strategy for a spray drying process according to an embodiment of the present invention; Figure 4 Flow chart for determining the qualification of the humid aging resistance of a cobalt salt adhesion promoter for an embodiment of the present invention. DETAILED DESCRIPTION

[0023] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0025] It should be pointed out that the data in this embodiment are obtained by comprehensive analysis and evaluation of the historical test data and the corresponding historical test results of the present invention three months before this test. It can be understood by those skilled in the art that the present invention can determine the above parameters for a single item by selecting the highest proportion of values ​​as the preset standard parameters according to the data distribution, using weighted summation to use the obtained values ​​as the preset standard parameters, substituting each historical data into a specific formula and using the values ​​obtained by the formula as the preset standard parameters or other selection methods, as long as the present invention can clearly define different specific situations in the single determination process through the obtained values.

[0026] See also Figure 1-Figure 4 As shown, Figure 1 This is a flow chart of a method for preparing a cobalt salt type adhesion promoter according to an embodiment of the present invention; Figure 2 A flow chart for determining the eligibility of a cobalt salt adhesion promoter to dryness for an embodiment of the present invention; Figure 3 A flow chart for determining a regulation strategy for a spray drying process according to an embodiment of the present invention; Figure 4 Flow chart for determining the qualification of the humid aging resistance of a cobalt salt adhesion promoter for an embodiment of the present invention.

[0027] The method for preparing a cobalt salt type adhesion promoter according to an embodiment of the present invention comprises: Step S1, in a reactor with a preset nitrogen introduction rate under a nitrogen environment, mixing a plurality of raw materials by stirring to fully mix the components to form a uniform mixed solution, wherein the raw materials include bisphenol A epoxy resin, a modifier, acetone, and a catalyst; Step S2, heating the mixed solution to a preset esterification reaction temperature and maintaining the temperature for a preset esterification time to perform an esterification reaction to obtain a modified bisphenol A epoxy resin; Step S3, cooling the modified bisphenol A epoxy resin to room temperature, and separating the modified bisphenol A epoxy resin from the unreacted raw material by distillation to obtain a purified modified bisphenol A epoxy resin solution; Step S4, mixing the modified bisphenol A epoxy resin solution with the cobalt boroacylate solution to obtain a reaction solution, heating the reaction solution to a preset coordination reaction temperature and maintaining the temperature for a preset coordination reaction time to perform a coordination reaction; Step S5, spray drying the reaction solution after the coordination reaction to obtain a cobalt salt adhesion promoter, and determining the eligibility of the drying of the cobalt salt adhesion promoter based on the color performance evaluation value of the cobalt salt adhesion promoter; Step S6, under the condition that the drying of the cobalt salt adhesion promoter is determined to be unqualified, determining the adjustment strategy of the spray drying process based on the state change evaluation value of the cobalt salt adhesion promoter, the adjustment strategy comprising increasing the drying pressure of the spray drying process or increasing the drying temperature of the spray drying process; Step S7, selecting a dried qualified cobalt salt adhesion promoter sample and placing it under preset relative humidity and preset temperature conditions for a preset time, performing a moisture aging resistance test on the cobalt salt adhesion promoter sample, and obtaining moisture aging resistance test data, calculating a moisture aging resistance effect characterization parameter according to the moisture aging resistance test data, and determining the qualification of the moisture aging resistance performance of the cobalt salt adhesion promoter; Step S8, when it is determined that the moisture aging resistance of the cobalt salt adhesion promoter is unqualified, adjusting the preset nitrogen introduction rate.

[0028] In the embodiment of the present invention, the modifier is at least one of nitrile rubber, chloroprene rubber, polyphenylene sulfide, and polyether sulfone, accounting for 30%-40% of the total amount, the ratio of bisphenol A epoxy resin to acetone is 10:1, and the bisphenol A epoxy resin and acetone account for 60%-70% of the total amount. The catalyst is p-toluenesulfonic acid and acetic acid, and the amount used is 0.1%-0.5% of the total amount of acetone, and p-toluenesulfonic acid and acetic acid are each 50% of the total amount of acetone, and the total amount is the mass of the mixed solution.

[0029] In the embodiment of the present invention, the spray drying process is to use a spray dryer to dry the cobalt salt adhesion promoter.

[0030] In the embodiment of the present invention, the reaction kettle can be any device that can perform chemical reactions, and is not specifically limited.

[0031] Specifically, the present invention can effectively remove oxygen and other impurity gases in a reaction system under a nitrogen environment, prevent reactants from reacting with oxygen in the air, and provide a stable, oxygen-free reaction environment for an esterification reaction. A plurality of raw materials are mixed to obtain a mixed solution, and an esterification reaction is performed. The mixed solution is then mixed with a cobalt borate solution to obtain a reaction solution. The reaction solution is spray-dried to obtain a cobalt salt adhesion promoter. The cobalt salt adhesion promoter is tested for its anti-wet aging performance, so that the cobalt salt adhesion promoter can still maintain excellent adhesion and mechanical properties in a humid environment, thereby improving the anti-wet aging performance of the cobalt salt adhesion promoter.

[0032] Specifically, in step S1, a plurality of raw materials are mixed and stirred in a reactor under a nitrogen environment at a preset nitrogen introduction rate to fully mix the components to form a uniform mixed solution, and the preset nitrogen introduction rate is 50 mL / min.

[0033] Specifically, in step S2, the mixed solution is heated to a preset esterification reaction temperature and maintained for a preset esterification time to perform an esterification reaction to obtain a modified bisphenol A epoxy resin. The preset esterification reaction temperature range is 80°C-100°C, and the preset esterification time is 2.5h.

[0034] Specifically, in step S3, the modified bisphenol A epoxy resin is cooled to room temperature, and the modified bisphenol A epoxy resin is separated from the unreacted raw material by distillation to obtain a purified modified bisphenol A epoxy resin solution, wherein the room temperature ranges from 20°C to 25°C.

[0035] Specifically, in step S4, the modified bisphenol A epoxy resin solution and the cobalt borate solution are mixed to obtain a reaction solution, and the reaction solution is heated to a preset coordination reaction temperature and maintained for a preset coordination reaction time to carry out a coordination reaction, wherein the preset coordination reaction temperature ranges from 60°C to 90°C, and the preset coordination reaction time is 2h.

[0036] Specifically, in step S5, the reaction solution is spray-dried to obtain a cobalt salt adhesion promoter, and the eligibility of the drying of the cobalt salt adhesion promoter is determined based on a comparison result of the color performance evaluation value of the cobalt salt adhesion promoter and a preset color performance evaluation value of 0.87; If the color performance evaluation value is less than or equal to the preset color performance evaluation value, it is determined that the drying of the cobalt salt adhesion promoter is unqualified; If the color performance evaluation value is greater than the preset color performance evaluation value, it is determined that the cobalt salt adhesion promoter is dried to a qualified level.

[0037] In the embodiment of the present invention, the preset color performance evaluation value is 0.87, and the preset color performance evaluation value is obtained by taking the average value of several historical color performance evaluation values ​​of the cobalt salt adhesion promoter that are qualified for drying, but the above value is not limited to this, and technical personnel in this field can also adjust the value according to actual needs.

[0038] Specifically, the embodiment of the present invention calculates the color performance evaluation value according to the following formula, setting: ; Among them, P represents the color performance evaluation value, S represents the color saturation of the cobalt salt adhesion promoter, L represents the brightness of the cobalt salt adhesion promoter, L0 represents the brightness of the dried and qualified cobalt salt adhesion promoter, and D represents the color spot of the cobalt salt adhesion promoter.

[0039] In the embodiments of the present invention, color saturation refers to the vividness of a color, and color spots refer to the degree of uneven color on the surface of an object, which can be obtained by comparing the dried cobalt salt adhesion promoter with a standard sample.

[0040] Specifically, the present invention sets esterification reaction conditions under nitrogen protection to ensure that bisphenol A epoxy resin and modifier fully react to form modified bisphenol A epoxy resin, introduces cobalt borate into the modified bisphenol A epoxy resin under set coordination reaction conditions, converts it into a cobalt salt adhesion promoter through spray drying technology, and uses color performance evaluation value to quickly dry the eligibility, so that the cobalt salt adhesion promoter can still maintain stable adhesion in a humid environment, thereby improving the anti-wet aging performance of the cobalt salt adhesion promoter.

[0041] Specifically, in step S6, under the condition that the drying of the cobalt salt adhesion promoter is determined to be unqualified, the adjustment strategy of the spray drying process is determined according to the comparison result between the state change evaluation value of the cobalt salt adhesion promoter and the preset state change evaluation value of 0.83; If the state change evaluation value is less than or equal to a preset state change evaluation value, determining to adjust the drying temperature of the spray drying process; If the state change evaluation value is greater than the preset state change evaluation value, it is determined to adjust the drying pressure of the spray drying process.

[0042] In the embodiment of the present invention, the preset state change evaluation value is 0.83, but the above value is not limited thereto, and those skilled in the art may also adjust the value according to actual needs.

[0043] Specifically, the embodiment of the present invention calculates the state change evaluation value according to the following formula, setting: ; Among them, Q represents the state change evaluation value, C represents the cobalt salt adhesion promoter curing hardness value, C0 represents the preset cobalt salt adhesion promoter curing hardness value, R represents the cobalt salt adhesion promoter particle dispersion uniformity value, and R0 represents the preset particle dispersion uniformity value.

[0044] In the embodiment of the present invention, C0 and R0 are pre-measured in experiments, and the curing hardness values ​​and particle dispersion uniformity values ​​of several cobalt salt adhesion promoters are obtained, and the average curing hardness value Ce and the average particle dispersion uniformity value Re are calculated. It is assumed that C0=a×Ce, a is the curing hardness value coefficient, 1.2<a<1.4, and R0=b×Re, b is the particle dispersion uniformity value coefficient, 0.9<b<1.1.

[0045] Specifically, under the condition of determining the temperature of the spray drying process to be adjusted, the embodiment of the present invention determines to increase the drying temperature of the spray drying process according to the comparison result between the preset state change evaluation value and the difference between the state change evaluation value and the preset difference value of 0.32; If the difference is less than or equal to the preset difference, it is determined to increase the drying temperature of the spray drying process to a corresponding value by a first preset temperature adjustment coefficient of 1.04; If the difference is greater than the preset difference, it is determined to increase the drying temperature of the spray drying process to a corresponding value using a second preset temperature adjustment coefficient of 1.09; The difference is the difference between the preset state change evaluation value and the state change evaluation value.

[0046] In the embodiment of the present invention, the preset difference value is 0.32, but the above value is not limited thereto, and those skilled in the art may also adjust the value according to actual needs.

[0047] In the embodiment of the present invention, the increased drying temperature of the spray drying process is set to Hz, and Hz=H×Ki is set, wherein H represents the drying temperature of the spray drying process, Ki represents the i-th preset temperature adjustment coefficient, i takes a value of 1 or 2, K1 is the first preset temperature adjustment coefficient, and K2 is the second preset temperature adjustment coefficient.

[0048] Specifically, the present invention adjusts the temperature or pressure in the spray drying process by comparing the state change evaluation value with the preset state change evaluation value, and further refines the temperature adjustment strategy according to the difference between the state change evaluation value and the preset value to ensure that the drying effect meets the standard. This adjustment strategy based on the state change evaluation value can accurately identify the reasons for unqualified drying and take targeted measures. Through the refined temperature adjustment coefficient, fine control of the spray drying process is achieved, effectively improving the drying efficiency and the quality of the cobalt salt adhesion promoter.

[0049] Specifically, the embodiment of the present invention determines to increase the drying pressure of the spray drying process according to the comparison result of the ratio of the preset state change evaluation value to the state change evaluation value and the preset ratio under the condition of determining to adjust the drying pressure of the spray drying process; If the ratio is less than or equal to the preset ratio, it is determined that the drying pressure of the spray drying process is increased to a corresponding value by using a first preset pressure adjustment coefficient of 1.13; If the ratio is greater than the preset ratio, it is determined that the drying pressure of the spray drying process is increased to a corresponding value by a second preset pressure adjustment coefficient of 1.17; The ratio is the ratio of the preset state change evaluation value to the state change evaluation value.

[0050] In the embodiment of the present invention, the preset ratio is 0.75, but the above value is not limited thereto, and those skilled in the art may also adjust the value according to actual needs.

[0051] In an embodiment of the present invention, the increased drying pressure of the spray drying process is set to Yz, and Yz=Y×Tj is set, wherein Y represents the drying pressure of the spray drying process, Tj represents the jth preset pressure adjustment coefficient, j takes a value of 1 or 2, T1 is the first preset pressure adjustment coefficient, and T2 is the second preset pressure adjustment coefficient.

[0052] Specifically, in step S7, a dried qualified cobalt salt adhesion promoter sample is selected and placed under preset relative humidity and preset temperature conditions. After a preset time, a moisture aging resistance performance test is performed on the cobalt salt adhesion promoter sample to obtain moisture aging resistance performance test data, and moisture aging resistance effect characterization parameters are calculated based on the moisture aging resistance performance test data, wherein the moisture aging resistance performance test data includes adhesion test data, hardness test data, and tensile strength test data, the preset relative humidity range is 70%-90%, the preset temperature range is 40°C-60°C, and the preset time is 40h-48h.

[0053] Specifically, the embodiment of the present invention calculates the moisture aging resistance effect characterization parameter based on the moisture aging resistance performance test data, and determines the eligibility of the moisture aging resistance performance of the cobalt salt adhesion promoter according to the comparison result of the moisture aging resistance effect characterization parameter and the preset moisture aging resistance effect characterization parameter 1.13; If the moisture aging resistance characterization parameter is less than or equal to the preset moisture aging resistance characterization parameter, it is determined that the moisture aging resistance performance of the cobalt salt adhesion promoter is unqualified; If the moisture-resistant aging effect characterization parameter is greater than the preset moisture-resistant aging effect characterization parameter, it is determined that the moisture-resistant aging performance of the cobalt salt adhesion promoter is qualified.

[0054] In the embodiment of the present invention, the preset value of the parameter characterizing the anti-humidity aging effect is 1.13, but the above value is not limited thereto, and those skilled in the art may also adjust the value according to actual needs.

[0055] Specifically, the embodiment of the present invention calculates the anti-humidity aging effect characterization parameter according to the following formula, and sets: ; Among them, E represents the parameter characterizing the anti-humidity aging effect, Z represents the adhesion test value, Zmax represents the maximum adhesion test value, Zmin represents the minimum adhesion test value, V represents the hardness test value, Vmax represents the maximum hardness test value, Vmin represents the minimum hardness test value, B represents the tensile strength test value, Bmax represents the maximum tensile strength test value, and Bmin represents the minimum tensile strength test value.

[0056] Specifically, the present invention conducts a moisture aging resistance test on a dried and qualified cobalt salt adhesion promoter, and evaluates its moisture aging resistance by comparing the test data with a preset standard, thereby ensuring the durability and stability of the cobalt salt adhesion promoter in the actual application environment. By simulating the hot and humid environment under actual use conditions, potential performance degradation problems can be discovered in advance, thereby improving the overall quality and reliability.

[0057] Wherein, in the step S8, under the condition that the moisture aging resistance of the cobalt salt adhesion promoter is determined to be unqualified, it is determined whether to adjust the preset nitrogen introduction rate according to the comparison result between the relative difference between the moisture aging resistance characterization parameter and the preset moisture aging resistance characterization parameter and the preset relative difference; If the relative difference is less than or equal to the preset relative difference, determining to increase the preset nitrogen introduction rate by the rate increase coefficient; If the relative difference is greater than the preset relative difference, determining not to adjust the preset nitrogen introduction rate; The relative difference is the relative difference between the parameter characterizing the anti-humidity aging effect and the preset parameter characterizing the anti-humidity aging effect.

[0058] In the embodiment of the present invention, the preset relative difference value is 0.23, but the above value is not limited thereto, and those skilled in the art may also adjust the value according to actual needs.

[0059] Specifically, the embodiment of the present invention determines the rate increase coefficient M1 according to the difference between the relative difference between the determined anti-humidity aging effect characterization parameter and the preset anti-humidity aging effect characterization parameter and the preset relative difference.

[0060] In the embodiment of the present invention, the increased preset nitrogen introduction rate is set as Nz, and Nz=N×M1 is set, wherein N represents the preset nitrogen introduction rate, and M1 represents the rate increase coefficient.

[0061] Specifically, the embodiment of the present invention calculates the rate increase coefficient according to the following formula and sets: ; Wherein, M1 represents the rate increase coefficient, ΔE represents the relative difference between the parameter characterizing the anti-humidity aging effect and the preset parameter characterizing the anti-humidity aging effect, and ΔE0 represents the preset relative difference.

[0062] Specifically, the present invention improves the moisture aging resistance of the unqualified cobalt salt adhesion promoter by adjusting the nitrogen introduction rate, so as to improve the cobalt salt adhesion promoter to maintain excellent adhesion performance in a humid environment, thereby improving the moisture aging resistance of the cobalt salt adhesion promoter.

[0063] Embodiment 1: (1) In a nitrogen environment with a nitrogen concentration of 10%, 591 g of bisphenol A epoxy resin, 59 g of acetone, 350 g of polyphenylene sulfide, 0.09 g of p-toluenesulfonic acid and 0.09 g of acetic acid were mixed to obtain a mixed solution; (2) continuously heating the mixed solution at 90° C. for 2.5 h to obtain a modified bisphenol A epoxy resin solution; (3) heating the modified bisphenol A epoxy resin solution and 1000 g of a cobalt borate solution having a cobalt content of 10% at 75° C. for 2 h to obtain a reaction solution; (4) The reaction solution is spray-dried to obtain a cobalt salt adhesion promoter.

[0064] Table 1 shows the physical and chemical performance parameters of the prepared cobalt salt adhesion promoter.

[0065]

[0066] The cobalt salt adhesion promoter was placed in an environment with a relative humidity range of 70%-90% and a temperature range of 40℃-60℃ for 46 hours to conduct a moisture aging resistance test, including an adhesion test, a hardness test, and a tensile strength test, to obtain adhesion test data, hardness test data, and tensile strength test data (Table 2).

[0067]

[0068] After increasing the nitrogen introduction rate, the optimized anti-humidity aging performance test data was obtained in a nitrogen environment with a nitrogen concentration of 12% (Table 3).

[0069]

[0070] Specifically, the cobalt salt adhesion promoter prepared by the preparation method of the present invention exhibits good performance retention ability in the moisture aging resistance test, especially after optimizing the nitrogen concentration, the moisture aging resistance is significantly improved.

[0071] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a cobalt salt type adhesion promoter, characterized in that: include: Step S1, in a reactor with a preset nitrogen introduction rate under a nitrogen environment, a plurality of raw materials are mixed and stirred to fully mix the components to form a uniform mixed solution, wherein the raw materials include bisphenol A epoxy resin, a modifier, acetone, and a catalyst; Step S2, heating the mixed solution to a preset esterification reaction temperature and maintaining the temperature for a preset esterification time to perform an esterification reaction to obtain a modified bisphenol A epoxy resin; Step S3, cooling the modified bisphenol A epoxy resin to room temperature, and separating the modified bisphenol A epoxy resin from the unreacted raw material by distillation to obtain a purified modified bisphenol A epoxy resin solution; Step S4, mixing the modified bisphenol A epoxy resin solution with the cobalt boroacylate solution to obtain a reaction solution, heating the reaction solution to a preset coordination reaction temperature and maintaining the temperature for a preset coordination reaction time to perform a coordination reaction; Step S5, spray drying the reaction solution after the coordination reaction to obtain a cobalt salt adhesion promoter, and determining the eligibility of the drying of the cobalt salt adhesion promoter based on the color performance evaluation value of the cobalt salt adhesion promoter; Step S6, under the condition that the drying of the cobalt salt adhesion promoter is determined to be unqualified, determining the adjustment strategy of the spray drying process based on the state change evaluation value of the cobalt salt adhesion promoter, the adjustment strategy comprising increasing the drying pressure of the spray drying process or increasing the drying temperature of the spray drying process; Step S7, selecting a dried qualified cobalt salt adhesion promoter sample and placing it under preset relative humidity and preset temperature conditions for a preset time, performing a moisture aging resistance test on the cobalt salt adhesion promoter sample, and obtaining moisture aging resistance test data, calculating a moisture aging resistance effect characterization parameter according to the moisture aging resistance test data, and determining the qualification of the moisture aging resistance performance of the cobalt salt adhesion promoter; Step S8, when it is determined that the moisture aging resistance of the cobalt salt adhesion promoter is unqualified, adjusting the preset nitrogen introduction rate.

2. The method for preparing a cobalt salt type adhesion promoter according to claim 1, characterized in that: In the step S1, the nitrogen introduction rate is preset to 50 mL / min.

3. The method for preparing a cobalt salt type adhesion promoter according to claim 1, characterized in that: In the step S2, the preset esterification reaction temperature range is 80° C.-100° C., and the preset esterification time is 2.5 h.

4. The method for preparing a cobalt salt type adhesion promoter according to claim 1, characterized in that: In step S3, the room temperature ranges from 20°C to 25°C.

5. The method for preparing a cobalt salt type adhesion promoter according to claim 1, characterized in that: In the step S4, the preset coordination reaction temperature range is 60° C.-90° C., and the preset coordination reaction time is 2 hours.

6. The method for preparing a cobalt salt type adhesion promoter according to claim 1, characterized in that: In step S5, based on the comparison result that the color performance evaluation value of the cobalt salt adhesion promoter is less than or equal to the preset color performance evaluation value, it is determined that the drying of the cobalt salt adhesion promoter is unqualified, and the color performance evaluation value is calculated according to the formula: , Among them, P represents the color performance evaluation value, S represents the color saturation of the cobalt salt adhesion promoter, L represents the brightness of the cobalt salt adhesion promoter, L0 represents the brightness of the dried and qualified cobalt salt adhesion promoter, and D represents the color spot of the cobalt salt adhesion promoter.

7. The method for preparing a cobalt salt type adhesion promoter according to claim 6, characterized in that: Under the condition that the drying of the cobalt salt adhesion promoter is determined to be unqualified, based on the comparison result that the state change evaluation value of the cobalt salt adhesion promoter is less than or equal to the preset state change evaluation value, it is determined to increase the drying temperature of the spray drying process, and according to the comparison result that the difference between the preset state change evaluation value and the state change evaluation value is less than or equal to the preset difference, it is determined to increase the drying temperature of the spray drying process by a preset temperature adjustment coefficient, and the state change evaluation value is calculated according to the formula, , Among them, Q represents the state change evaluation value, C represents the cobalt salt adhesion promoter curing hardness value, C0 represents the preset cobalt salt adhesion promoter curing hardness value, R represents the cobalt salt adhesion promoter particle dispersion uniformity value, and R0 represents the preset particle dispersion uniformity value.

8. The method for preparing a cobalt salt type adhesion promoter according to claim 6, characterized in that: Under the condition that the drying of the cobalt salt adhesion promoter is determined to be unqualified, it is determined to increase the drying pressure of the spray drying process based on the comparison result that the state change evaluation value of the cobalt salt adhesion promoter is greater than the preset state change evaluation value, and it is determined to increase the drying pressure of the spray drying process by a preset pressure adjustment coefficient based on the comparison result that the ratio of the preset state change evaluation value to the state change evaluation value is less than or equal to the preset ratio.

9. The method for preparing a cobalt salt type adhesion promoter according to claim 1, characterized in that: In step S7, the moisture aging resistance test data includes adhesion test data, hardness test data, and tensile strength test data. The preset relative humidity range is 70%-90%, the preset temperature range is 40°C-60°C, and the preset time is 40h-48h.

10. The method for preparing a cobalt salt type adhesion promoter according to claim 9, characterized in that: Based on the comparison result that the anti-moisture aging effect characterization parameter is less than or equal to the preset anti-moisture aging effect characterization parameter, it is determined that the anti-moisture aging performance of the cobalt salt adhesion promoter is unqualified, and based on the comparison result that the relative difference is less than or equal to the preset relative difference, it is determined to increase the preset nitrogen introduction rate by the rate increase coefficient, and the relative difference is the relative difference between the anti-moisture aging effect characterization parameter and the preset anti-moisture aging effect characterization parameter.

Citation Information

Patent Citations

  • Preparation of organic cobalt salt adhesion promotion agent

    CN101481591A

  • Compound rubber bonding promoting agent and preparation method thereof

    CN102585294A

  • Adhesion promoter for aqueous coating compositions

    CN106459301A

  • Adhesive for tire rubber and preparation method thereof

    CN107011847A

  • Rubber composition for tire steel cord

    KR1020010106733A